Research on antidepressants in India - Avasthi, Ajit (Medknow Publications, 2010)
Data suggests that antidepressants are useful in the management of depressive disorders, anxiety disorders, sexual dysfunction, eating disorders, impulse control disorders, enuresis, aggression and some personality disorders. Research focusing on the usefulness of antidepressants in India has more or less followed the trends seen in the West. Most of the studies conducted in India have evaluated various antidepressants in depression. In this article, we review studies conducted in India on various antidepressants. The data suggests that antidepressants have been evaluated mainly in the acute phase treatment and rare studies have evaluated the efficacy in continuation phase treatment.